2022
DOI: 10.4018/978-1-6684-6762-6.ch011
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Digital Transformation Strategies of Large Suppliers for Mexican Corner Stores During a Pandemic

Abstract: With the pandemic, digital transformation (DT) was accelerated, and consumers adopted new consumption patterns. Therefore, suppliers had to adapt their business models quickly. This study aims to understand the strategies of large suppliers on Mexican corner stores (CS) during the pandemic and show the perception of CS about these DT strategies. Many digital platform initiatives that were developed by both the government and large suppliers are introduced in this chapter. Additionally, interviews with large su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Anderson (2022) concludes that the largest improvements come from the initial few modernizing changes, after which returns are diminishing [85]. It was demonstrated that large companies developed digital transformation strategies to promote corner stores continuity [87] and the introduction of technology in companies becomes a necessity to continue their activities and avoid definitive closure [86].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anderson (2022) concludes that the largest improvements come from the initial few modernizing changes, after which returns are diminishing [85]. It was demonstrated that large companies developed digital transformation strategies to promote corner stores continuity [87] and the introduction of technology in companies becomes a necessity to continue their activities and avoid definitive closure [86].…”
Section: Discussionmentioning
confidence: 99%
“…Focused on micro and small companies, the authors maintain that those companies that changed their activities to online sales increased with respect to their activities before the pandemic [86]. Digital transformation strategies for corner stores during the pandemic were analyzed [87]. Carrying out the empirical research in multiple companies from technologically advanced sectors in Mexico (automotive, aerospace and services) made it possible to explore the conditions of the analog to digital transformation process [88].…”
Section: Caveatsmentioning
confidence: 99%